2 Answers By Expert Tutors
Now that is given Y explicitly in term of X , it is better off using substitution method
Y = 2X -6
3X + y = 4
3X + 2X - 6 = 4
5X = 10
X = 2
Y = 2( 2) - 6 = -2
First, you want to plus the first equation into the second one.
It says that y=2x-6 so we plug (2x-6) where ever we see a y in the second equation:
3x + 2x -6 = 4 -> 5x-6=4
5x=10 -> x=2
Now that we have the x-value, we can plug this back into any equation.
3(2)+y=4 -> y=-2
Still looking for help? Get the right answer, fast.
Find an Online Tutor Now
Choose an expert and meet online.
No packages or subscriptions, pay only for the time you need.